Recycled waste materials in concrete construction emerging research and opportunities - Mirza, Jahangir 1944-; Hussin, Mohd Warid 1951-; Ismail, Mohamed A. 1968- (IGI Global, 2019)
"This book discusses the different type of industrial, agricultural and/or natural wastes and how some have been already utilized in the concrete industry while many others demonstrate promise for future use"--